2008
DOI: 10.1002/ajp.20592
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional diversity of mouse lemurs (Microcebus spp.) in the Makira region with the description of one new species

Abstract: 4Durrell Wildlife Conservation Trust-Madagascar, Antananarivo, Madagascar Although the number of described lemur species has increased considerably over the last 20 years, detailed biogeographic data are still lacking from many geographic regions, in particular in the eastern part of Madagascar. This study investigated mouse lemur species diversity in a previously unstudied Inter-River-System in the eastern Makira region. Three sites were visited and 26 individuals were sampled and characterized with 13 extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
(29 reference statements)
0
47
0
2
Order By: Relevance
“…Louis et al (2006a) identified 2 differentiated forms in the southern part of the range of Microcebus jollyae, and consider its distribution only temporary as more information becomes available. In the Makira region, Microcebus mittermeieri is sympatric with 2 other mouse lemurs, one of which Radespiel et al (2008) described as Microcebus macarthurii, but the other remains undescribed owing to small sample size. Louis et al (2006a) also found that the mouse lemur from the island of Nosy Be in the northwest, west of the Manongarivo Special Reserve, was divergent from the mainland species there, Microcebus sambiranensis.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
See 1 more Smart Citation
“…Louis et al (2006a) identified 2 differentiated forms in the southern part of the range of Microcebus jollyae, and consider its distribution only temporary as more information becomes available. In the Makira region, Microcebus mittermeieri is sympatric with 2 other mouse lemurs, one of which Radespiel et al (2008) described as Microcebus macarthurii, but the other remains undescribed owing to small sample size. Louis et al (2006a) also found that the mouse lemur from the island of Nosy Be in the northwest, west of the Manongarivo Special Reserve, was divergent from the mainland species there, Microcebus sambiranensis.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
“…Morphological and (especially) cytogenetic and molecular genetic studies are resulting in some major changes in our understanding of the diversity, phylogeny, and systematics of the lemurs (Fausser et al 2002;Mayor et al 2004;Ravoarimanana 2001;Rumpler 2000Rumpler , 2004, as well as the identification of numerous new species (Andriaholinirina et al 2006a;Andriantompohavana et al 2006Andriantompohavana et al , 2007Craul et al 2007;Kappeler et al 2005;Lei et al 2008;Louis et al 2006a, b;Olivieri et al 2007;Rabarivola et al 2006;Radespiel et al 2008;Rasoloarison et al 2000;Rylands et al 2002;Geissmann 2000, 2005;Zaramody et al 2006;Zimmermann et al 1998). Groves and Tattersall (1991), Groves (2000Groves ( , 2001Groves ( , 2005Groves ( , 2007, and Groves and Helgen (2007) revised existing museum material intensively.…”
mentioning
confidence: 99%
“…The mouselemurs of the genus Microcebus were thought to comprise a single broadly distributed species, until Martin (1972) recommended that a second form should be recognized. Subsequently, largely molecular studies revealed considerable fixed genetic differences and, as of September 2008, at least 19 species are proposed that are phenotypically similar to one another (Rasoloarison et al, 2000;Kappeler et al, 2005;Louis et al, 2006Louis et al, , 2008Olivieri et al, 2007;Radespiel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…vários trabalhos se dedicaram a reexaminar os caracteres morfológicos dos Lemuriformes buscando por apomorfias e diferenças consistentes entre eles que pudessem contar sua história evolutiva (Cartmill, 1975;Groves, 1974;Groves and Trueman, 1995;Groves and Eaglen, 1988;Schwartz and Tattersall, 1985;Szalay and Katz, 1973;Szalay et al, 1987;Tattersall and Schwartz, 1974, 1991 (Groves, 2001;Nekaris and Bearder, 2007;Radespiel et al, 2008;Tattersall, 2007;Yoder, 2012). Esses números refletem a recente explosão de trabalhos de campo e estão potencialmente relacionados a fins de conservação, mas também conduziram a uma inflação taxonômica (Tattersall, 2007).…”
Section: Identificaçãounclassified
“…No decorrer das últimas duas décadas o número de espécies de Lemuriformes reconhecidas triplicou (chegando a uma centena Mittermeier et al, 2010), sendo que muitas delas apresentam diversi-5 dade críptica ou tratam-se de subespécies (Groves, 2001;Nekaris and Bearder, 2007;Radespiel et al, 2008;Tattersall, 2007;Yoder, 2012). Esses números refletem a recente explosão de trabalhos de campo e estão potencialmente relacionados a fins de conservação, mas também conduziram a uma inflação taxonômica (Tattersall, 2007).…”
Section: Identificaçãounclassified